“LOST AND FOUND BOX” AS A SCHOOL INNOVATION IN STRENGTHENING THE CHARACTER OF STUDENTS BASED ON INTEGRITY VALUES IN ELEMENTARY SCHOOL - Maisyaroh, Maisyaroh; Untari, Sri; Chusniyah, Tutut; Prestiadi, Dedi; Adha, Maulana Amirul; Ariyanti, Nova Syafira; Saputra, Bagus Rachmad; Yulaidi, Endrik Mas (Faculty of Education Universitas Negeri Malang, 2022)
Current education programs are directed at the implementation and strengthening of character education in schools. Character education is considered the right solution to solve the problems of the Indonesian nation. The purpose of this study was to determine the planning process for strengthening character education based on integrity values in schools, the implementation of the lost and found box program in schools, and the impact of implementing the lost and found box program in schools. This study used a qualitative descriptive research design with a case study approach. The data collection techniques used in this study were interviews and documentation studies. This research was conducted at Elementary School Laboratory Universitas Negeri Malang, Blitar City, with the principal as the key informant and teacher, education staff and school committee as additional informants. The results of this study shows that planning activities in the integrity value-based character education strengthening program have been divided into learning and non-learning aspects. Program planning is carried out through work meetings involving school principals, teachers, education personnel, parents, school committees, stakeholders, education experts, with the principal as the highest decision maker. The impact of implementing the